Do Executive Facial Trustworthiness Have Impact on IPO Underpricing? - Hendrawan, I Putu Sukma; Utama, Cynthia (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
This study is aimed at investigating the impact of facial-based perceived trustworthiness on stock valuation, particularly in the initial public offering (IPO). IPO settings provide opportunity to investigate whether information asymmetry resulted from company newness in the market would influence the incorporation of soft information in the form of executive facial trustworthiness in stock valuation. This study use recent machine learning algorithm to detect facial landmarks and then calculate a composite facial trustworthiness measure using several facial features that has previously been observed in neuroscience and psychological study to be the most determining factor of perceived trustworthiness. Employing 312 IPO samples in the Indonesia Stock Exchange between 2018 to August 2023, this study find that the facial trustworthiness of the company executive negatively impacts the extent of IPO underpricing. This result implies that investors incorporate the facial trustworthiness of company executives into stock valuation. This study provides evidence on the impact of top management cognitive characteristics on firms’ financial transactions in the Indonesian context. From the perspective of investors and other fund providers, this study shows evidence that heuristics still play an important role in financial decision making. This is also an indication of investor reliance on soft information. Our research method also provides a new opportunity for the use of machine-learning algorithms in processing non-conventional types of data in finance research, which is still relatively rare in emerging market like Indonesia. To the best of our knowledge, our study is the first to use personalized-measure of trust generated through machine-learning algorithms in IPO settings in Indonesia.